Constructing Women's Right to Justice in Indonesian and American Criminal Law: A Comparative Study - Fatimah Hasan Haini; Hervin Yoki Pradikta (Journal of Islamic Mubadalah, 2024)
This article analyses women's justice rights in criminal law regulation and in relation to criminal punishment. This article is a comparative study between Indonesia and America (Ecuador and Argentina). The conception of human rights is echoed in the international world, but the status of women is still experiencing injustice in the application of law. The purpose of this article is to analyse the construction of Indonesian and American criminal law in providing justice rights for women. The approach used is qualitative, library research, data sources are taken from existing criminal law literature in Indonesia and America. The approach used is a normative study that explores the norms in criminal law in the two countries. The results show that Indonesian criminal law still leaves gender bias articles, the implication is that women suffer from vulnerability in the law. Criminal law in America is also the same, although America has passed the Second Chance Act, Fair Sentencing Act, and First Step Act women and girls are more likely to get legal sanctions than men, patriarchy and skin colour still seem to be high factors. Offences such as intimate partner violence, both physical and psychological